Cholera: An Outbreak Causing Diarrhoea; A Serious Threat to Population - Romah Ishfaq, S. M. Abbas Naqvi, Mehvish Javeed, Atif Zulfiqar, Hubza Ruatt Khan, Ahsanullah M Mirbahar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the association of Vibrio cholera infection with age and gender. To develop the antibiotic sensitivity pattern for Vibrio cholera against commercially available preparations in market. Study Design: Descriptive cross-sectional Place and duration: Study was conducted at department of Pathology, Nishtar Medical University and Hospital Multan, in the months from April to September, 2022. Methodology: Total 191 Stool samples were sent to Microbiology laboratory, Pathology department of hospital which was included in this study. These samples were from Nishtar Hospital various wards and from CEO office. After successful isolation of bacteria the antibiotic sensitivity were tested by Kirby-Baur Disc Diffusion Method. Results: During the outbreak of Vibrio cholera in our area, 10.99% cases were detected in whole diseased population. Mean age of patients who developed Vibrio cholera was 7.68 + 0.66 years. Gender showed no discrimination as both males and females were almost equally affected. Age and gender were not found statistically significant (p=0.740 and p=0.329). The sensitivity was measured for three antibiotic drugs (Ampicillin, Erythromycin and Tetracycline). Among them only Ampicillin showed 50% sensitivity whiles other two antibiotics were 100% sensitive. Conclusion: Unhygienic environment especially in pediatrics group has showed to be the main risk factor in the outbreaks of cholera. Proper disposal of waste, especially from infected persons, to keep it segregated from drinking water along with awareness programs are the need of hour to prevent further outbreaks. Keywords: Kirby-Baur Disc Diffusion Method, Vibrio cholera, Outbreak, Pediatrics, Ampicillin, Erythromycin and Tetracycline